Southern Hemispheric jet swing linked to Arctic stratospheric polar vortex - Fei Xie; Xuan Ma; Yanjie Li; Jianping Li; Xiaosong Chen; Wenshou Tian; Cheng Sun; Mian Xu; Jiankai Zhang; Ke Gui; Ruiqiang Ding; Yan Xia; et al. (Environmental Research Letters, 2024)
Our study reframes our understanding of stratosphere–troposphere interactions, traditionally thought to be confined within individual hemispheres, by introducing a novel cross-hemispheric link. We demonstrate that strong boreal winter Arctic stratospheric polar vortex (APV) boosts the transmission of upper tropospheric waves from Northern Hemisphere’s mid-high latitudes to the equator. Facilitated by the tropical central and eastern Pacific’s ‘westerly bridge’, these waves reach Southern Hemisphere’s mid-high latitudes. The entire process shows a ‘semicircular road’. Waves reaching the Southern Hemisphere affect the circulation through wave-flow interaction, causing a southward swing of the Southern Hemispheric westerly jet center. This displacement weakens the subtropical jet and strengthens the polar jet, resulting in increased subtropical precipitation and decreased mid-latitude precipitation in the Southern Hemisphere during austral summer. Correspondingly, a weak APV may lead to the opposite result. Our findings underscore APV’s broader impact on the tropospheric atmosphere, extending beyond prior knowledge.